Integrating educational technology into mathematics instruction for students with dyscalculia: Mathematics teachers’ perspective - Bagazi , Afrah Salem (Journal of Education and e-Learning Research, 2025)
The present quantitative study examines the perspectives of mathematics teachers towards the benefits, uses, and challenges of incorporating educational technologies into mathematics teaching to aid primary school students with dyscalculia in Saudi Arabia’s Al-Kharj province. Moreover, data in this study were collected by a survey from 160 mathematics teachers who taught students with dyscalculia. The findings indicate that there are many advantages of employing educational technologies and high usage of such technologies in real educational settings, but still, several challenges are associated with their implementation. Furthermore, no statistically significant differences could be identified regarding gender, academic qualification, and years of experience concerning the advantages, the realities of using technology, and the challenges. Nonetheless, a statistically significant difference was identified between the variables of advantages, realities of using technology, and challenges, and the number of educational technology training courses that the teachers had attended. Mathematics teachers who had attended at least one session demonstrated higher scores for the advantages and realities of using educational technology, whereas those who had not attended any courses highlighted more challenges with the implementation of educational technologies to help students with dyscalculia. This study offers valuable insights into educational technologies among primary school students with dyscalculia.